2022
DOI: 10.1002/gj.4654
|View full text |Cite
|
Sign up to set email alerts
|

Role of sustainable finance, geopolitical risk and economic growth in renewable energy investment: Empirical evidence from China

Abstract: The global economic recession caused by COVID‐19 has posed a severe threat to the feasibility of renewable energy projects, hampering the United Nation (UN) sustainable development goals. Sustainable financing (SF) is a crucial instrument for promoting investment in renewable energy (IRE) sources, as it is regarded as a crucial aspect in achieving long‐term sustainability. This study sheds insight on the impact of SF, geopolitical risk (GPR), economic growth (EG), and environmental regulation (ER) on IRE sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Most developed nations are eliminating their non‐renewable sources with innovative financial approaches (Ali et al, 2022). Because of environmental regulations and less competitive pressures in the financial industry, the research revealed that FNI tends to encourage green initiatives (Lin et al, 2022). The present research evaluates, from the standpoint of the BRICS‐T economies, whether FNIs produce favourable or unfavourable (positive or negative) impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Most developed nations are eliminating their non‐renewable sources with innovative financial approaches (Ali et al, 2022). Because of environmental regulations and less competitive pressures in the financial industry, the research revealed that FNI tends to encourage green initiatives (Lin et al, 2022). The present research evaluates, from the standpoint of the BRICS‐T economies, whether FNIs produce favourable or unfavourable (positive or negative) impacts.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of green money has continually exhibited a bias towards investment in wind and biomass energy, offering significant benefits to the RE industry (An et al, 2023). GF aims to alleviate the financial strain of RE generation by offering economic incentives through direct or indirect means (Lin et al, 2022). In their study on China's sustainable growth and production-based CO 2 emissions spanning from 1998 to 2017 (Khan et al, 2020) investigated the influence of green investment.…”
Section: Green Finance and Environmental Sustainabilitymentioning
confidence: 99%
“…The first factor to emerge from this special issue was the geopolitical situation which refers to the state of economic, social and political affairs in a particular region (Lin et al, 2023; Wei et al, 2023). According to Lin et al (2023), geopolitical risk (GPR) is a major hurdle in promoting sustainable development projects, green investments and global stability and arises due to the interaction between nations and regions.…”
mentioning
confidence: 99%
“…Feng and Fu (2023) The third factor highlighted by this special issue was the region's economic situation, including economic growth, inflation, trade ratio, job and income level and monetary and fiscal policies. Lin et al (2023) linked national economic growth with regional potential to invest in renewable energy sources. They explained that if a region's economy grows, more entities will invest in clean energy projects, which ultimately will help the region mitigate climate change challenges.…”
mentioning
confidence: 99%
See 1 more Smart Citation